Is Instagram an effective brand conversation platform? A study among young Instagram users in India. (21st January 2021) - Narsimha, Anand; Moovendhan, V.; Manoharan, M.
Instagram generally perceived to be a brand engagement than brand awareness medium. The research aimed at investigating the most influencing variable among various brand equity concepts such as brand awareness, brand association, brand loyalty and perceived quality of Instagram users in India. Though numerous researches explored Facebook and Twitter users on this context, there is little research on Instagram despite being the emerging visual communication medium. The result of this survey-based research indicates that young users perceive the brand circulated on Instagram as quality, followed by brand loyalty and brand association. The brand awareness had a subtle relationship with overall brand equity, and this result asserts that Instagram is perceived as better of brand engagement tool than brand awareness medium while building brand equity for a product.